The Relationship Between Personal Hair Hygiene and The Incidence of Pityriasis Capitis in Students at Faculty of Medicine, Baiturrahmah University - Marsa Qalbina Abdi; Irma Primawati; Dessy Abdullah (Biomedical Journal of Indonesia, 2025)
Introduction. Pityriasis capitis or commonly known as dandruff, pityriasis sicca, pityriasis simplex is a disorder resulting from mild inflammation caused by excessive exfoliation of the stratum corneum which is characterized by the presence of white-gray flakes on the scalp and hair shaft. Personal hygiene, including self-care carried out by a person to protect and maintain their health. Aim the research to the relationship between personal hair hygiene and the incidence of pityriasis capitis in students at Faculty of Medicine, Baiturrahmah University. Methods. This study is quantitative research that applies an analytical approach by design cross-sectional. The research participants came from students at the Faculty of Medicine, Baiturrahmah University and total of 108 samples were selected using techniques consecutive sampling. The data in this study is primary data obtained from the results of questionnaires and scalp observations. Data analysis used SPSS version 25 and the test used was chi-square test. Results. Students who experience pityriasis capitis are 66 people (61.1%) with the largest gender experience it being women, namely 46 people (42.6%). Personal hair hygiene of students are in the medium category, namely 76 students (70.4%). There is a relationship between personal hair hygiene and the incidence of pityriasis capitis with a p-value of 0.029 (p<0.05). Conclusion. There is a relationship between personal hair hygiene and the incidence of pityriasis capitis in students at the Faculty of Medicine, Baiturrahmah University.